Benefits and limitations of acoustic methods in the vehicle transmission diagnostics: A case study - Kriston, József Balázs; Jálics, Károly (Design of Machines and Structures, 2021)
In general, for the diagnostics of a faulty machine several diagnostic methods can be considered. In this paper, the benefits and limitations of the acoustic diagnostic methods are shown, based on a noise problem of a real car with a 6-speed manual transmission. The possible diagnostic methods will be pointed out, and an analysis will be performed with noise and vibration measurements on the car. Based on the analysis conclusions regarding the benefits and limits of the used diagnostic method will be drawn.